Probing cold nuclear matter effects with the productions of isolated- and +jet in p+Pb collisions at 8.16 TeV *Supported by the NSFC of China (11435004, 11322546, 11805167) and partly Supported by China University of Geosciences (Wuhan) (162301182691). (April 2019) - Ma 马, Guo-Yang 国扬; Dai 代, Wei 巍; Zhang 张, Ben-Wei 本威
Abstract: We investigate cold nuclear matter (CNM) effects on the productions of isolated prompt photons and jet in proton-lead collisions at TeV under next-to-leading order perturbative quantum chromodynamics calculations with four parameterizations for nuclear parton distribution functions (nPDFs), i.e., DSSZ, EPPS16, nCTEQ15, and nIMParton. Our theoretical calculations provide good descriptions of the pp baseline in the ATLAS collaboration and make predictions for future experimental results at + collisions. We calculate the dependence of the nuclear modification factor of isolated prompt photons on transverse momentum and pseudo-rapidity at very forward and backward rapidity regions, and we demonstrate that the forward-to-backward yield asymmetries as a function of with different nPDF parameterizations have diverse behaviors. Furthermore, the nuclear modification factor of isolated- jet as a function of jet's pseudo-rapidity at different average transverse momenta has been discussed. This can facilitate a tomographic study of CNM effects with precise locations in a rather wide kinematic region by varying the transverse momenta and rapidities of both isolated photons and jets in p+A collisions.